Reimagining sustainable urban communities in Hong Kong - VAN AMEIJDE, Jeroen (Institutional Knowledge at Singapore Management University, 2023)
Using environmental and social urban design principles to create future new towns. Hong Kong began building New Towns in the 1970s in response to a post-war period of rapid population growth.